An Analysis of the Putative CBD Binding Site in the Ionotropic Cannabinoid Receptors - Muller, Chanté; Reggio, Patricia H. (Frontiers in Cellular Neuroscience, 2020)
Cannabinoids have been long studied for their therapeutic properties, especially for their use in pain management. As new therapies are sought after to treat chronic pain conditions, so is a better understanding of the ligands and their target receptors or channels. A recently published cryo-EM structure showed the putative binding location of a well-known cannabinoid ligand, cannabidiol (CBD), in TRPV2, a channel that has been implicated in inflammation and chronic pain. TRPV2, along with TRPV1, TRPV3, TRPV4, TRPA1, and TRPM8 all have the capability to be modulated by cannabinoid ligands and are located in the peripheral nervous system. Here, we analyze the putative CBD binding site in each of these channels and compare structural and sequential information with experimental data.